A theoretical review of land use characteristics on the use of rail-based public transport in Kuala Lumpur - Bakri, Fatahsha Amira; Kadar Hamsa, Abdul Azeez (2018)
The increase of population and rapid urbanization have contributed to the increase of travel in major urban areas which leads to urban mobility problems such as traffic congestion. Increasing road infrastructure supply to cater for the increase in travel demand especially by private vehicle use may not necessarily address the congestion problems in the long run. Moreover, the increase in road infrastructure in major towns and cities requires adequate land, economic and other related resources which are always not possible to provide for. Thus, public transport is one of the viable solutions that can be considered in addressing the increase in travel demand especially in urban areas. However, the increase in travel distance along with the disaggregated spread of major land use activities and limited public transport services has induced commuters to use private transportation, especially cars for work and business trip. The aim of this paper is to synthesize and critically evaluate the effects of land use density and diversity on rail-based public transport ridership from literature review. This paper analyses the existing literature on Transit-Oriented Development (TOD), its elements and characteristics as well as its successful application in few selected countries to ascertain the extent of land use characteristics effects on the use of rail-based public transport.